2012
DOI: 10.3727/096368911x623853
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Ischemic Preconditioning on Pancreas Cold Preservation

Abstract: Ischemic preconditioning (IPC) confers tissue resistance to subsequent ischemia in several organs. The protective effects are obtained by applying short periods of warm ischemia followed by reperfusion prior to extended ischemic insults to the organs. In the present study, we evaluated whether IPC can reduce pancreatic tissue injury following cold ischemic preservation. Rat pancreata were exposed to IPC (10 min of warm ischemia followed by 10 min of reperfusion) prior to ~18 h of cold preservation before asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 68 publications
(129 reference statements)
1
22
0
Order By: Relevance
“…Furthermore, the presence of increased ER stress in human islets during islet isolation has been reported (28), which may also influence BBC3-mediated islet death. It has been reported that several conditions, such as ischemic preconditioning of rat pancreata (10), ductal injection of a p38 mitogen-activated protein kinase inhibitor in canine pancreata (14), and c-Jun NH 2 -terminal kinase inhibitor in porcine pancreata (30), improve islet yield and decrease apoptosis of isolated islets. How these treatments affect on Bbc3/BBC3-mediated islet death is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of increased ER stress in human islets during islet isolation has been reported (28), which may also influence BBC3-mediated islet death. It has been reported that several conditions, such as ischemic preconditioning of rat pancreata (10), ductal injection of a p38 mitogen-activated protein kinase inhibitor in canine pancreata (14), and c-Jun NH 2 -terminal kinase inhibitor in porcine pancreata (30), improve islet yield and decrease apoptosis of isolated islets. How these treatments affect on Bbc3/BBC3-mediated islet death is not known.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, most of the time, islets from at least two human pancreata are needed to reverse diabetes in a type-1 patient (6,9,50) evidencing that some major limitations to this procedure and its clinical applicability still exist. A limited number of islets can be isolated from a human pancreas even under optimal circumstances (i.e., optimal donor) (13,16,19,42). In addition, factors not completely known seem to be responsible for loss of islet functionality in the immediate post-transplant period and/or over time (13).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors can involve autoimmunity (18,50,59), rejection (48), immunosuppression toxicity (31,36,58), and post-transplant inflammatory conditions (22). Significant attention has been directed toward the development of strategies to improve organ retrieval and islet isolation (2,16,19,20) and although both have been improved over time, protocols and products are not completely standardized. It is known that following transplantation (and/or culture) from 30–60% of the islets can be lost (8,15).…”
Section: Introductionmentioning
confidence: 99%
“…3e5 Mechanisms underlying early effects of IP have been elucidated to some extent in terms of complex roles for multiple mediators (including adenosine, ATP, and nitric oxide) that may engage receptors and/or intracellular signaling pathways and transcription factors, such as p38 MAPK, NF-kB, and mitogenactivated protein kinase 8 [MAPK8; alias c-Jun N-terminal kinase (JNK)]. 6,7 However, these studies have been limited to only the initial minutes or hours after IP, and thus the late effects of IP (including the long-term fate of cells exposed to IP) and potential mechanisms causing such effects are not understood. The need for such understanding becomes critical in terms of therapeutic implications of IP in tissue protection for organ transplantation and regeneration, and also for cell therapy.…”
mentioning
confidence: 99%
“…IP induces antioxidant protection, 6,7 and this should be relevant because intravascular injection of cells may cause IR, along with immediate blood-mediated responses, release of vasoactive peptides, cytokines, and chemokines from activated neutrophils, macrophages, and other cells, variously resulting in oxidative stress and clearance of transplanted cells. 18,19 Similarly, oxidized extracellular matrix components impair cell survival through outsideein NF-kBerelated signaling, which could possibly be altered by IP.…”
mentioning
confidence: 99%